A proposal of Multimedia Steganography Algorithm based on Improved Least Significant Bit (LSB) Method - Dheyauldeen Najeeb, Huda; Tahseen Ali, Israa (Iraqi Journal of Science, 2021)
Because of the rapid development and use of the Internet as a communication media emerged to need a high level of security during data transmission and one of these ways is "Steganography". This paper reviews the Least Signification Bit steganography used for embedding text file with related image in gray-scale image. As well as we discuss the bit plane which is divided into eight different images when combination them we get the actual image. The findings of the research was the stego-image is indistinguishable to the naked eye from the original cover image when the value of bit less than four Thus we get to the goal is to cover up the existence of a connection or hidden data. The Peak to Signal Noise Ratio(PSNR) and Mean Square Error (MSE) value is calculated so that the quality of the cover image before and after the data hiding is evaluated.